Localization of ecdysterone on polytene chromosomes of Drosophila melanogaster. - Gronemeyer, H (1980)
Ecdysterone has been crosslinked in situ to polytene chromosomes of salivary glands of Drosophila melanogaster by photoactivation. The crosslinked hormone has been localized on the chromosomes by indirect immunofluorescence microscopy. At different developmental stages the hormone was detected at different chromosomal loci. These chromosomal sites correspond to ecdysterone-inducible puff sites. Thus, the hormone binds directly to chromosomal loci, whose transcription depends on the presence of the hormone. Ecdysterone was also crosslinked to one puff site that regresses during larval development. This indicates that (i) hormone binding to polytene chromosomes activates transcription at specific loci, and (ii) hormone-dependent regression of intermolt puff 68C is mediated by direct binding of ecdysterone. Ecdysterone was not detected on puff sites that are independent of hormone action or in chromosomal interbands. After heat shock, no ecdysterone became crosslinked to polytene chromosomes.